P221 Drug survival of biologics in ulcerative colitis treatment in Norway. (25th January 2019) - Lirhus, S S; Lie Høivik, M; Moum, B; Melberg, H O
Abstract: Background: Real-world treatment patterns of biologics remains largely unknown. We aimed to investigate the drug survival of biologics in a national cohort of patients with ulcerative colitis (UC). Methods: Data were collected from the Norwegian Patient Registry (NPR) and the Norwegian Prescription Database. The study cohort was defined as all patients with at least two diagnosis of K51 (UC) in NPR from 2010 to 2017 with no prior IBD diagnosis in NPR (data from 2008). Treatment for patients who only received one infusion of VDZ or IFX before discontinuing treatment was not included in the analysis to exclude false registrations. VDZ is not given as first-line biologic treatment in Norway due to the tender process. Kaplan–Meier time‐to‐event analyses were performed to estimate time to treatment discontinuation. Discontinuation was defined as 3 months without a new infusion or prescription of the current drug after the predefined DDD period for the drug (ie, medication gap of >90 days). Biologic survival was compared using the log-rank test. The proportion of patients that received methotrexate or azathioprine was estimated by looking at the number of patients who received a prescription 6 months prior to or after starting biologic treatment. The χ 2 test was used to compare the proportions receiving immunomodulators. Patients were followed until the outcomes of interest, death, or end of follow-up (31 December 2017), whichever occurred first. Results: In total, 2113 UC patients were included in the study. After 3 years, the survival rate of first-line biologics for UC patients was 42.7% for IFX, 28.7% for ADA and 33.7% for GOL. GOL and IFX survival was significantly different from ADA ( p < 0.001). First-line biological therapy survival UC. For second-line treatment, the survival rates were 35.9% for IFX, 32.3% for ADA, 43.7% for GOL and 58.8% for VDZ. GOL and VDZ survival was significantly different from ADA ( p < 0.01 and p < 0.001). VDZ survival was also significantly different from IFX ( p < 0.001). Second-line biological therapy survival UC. Six months before or after starting treatment 65.1% (IFX), 57.4% (ADA) and 49.5% (GOL) received an immunomodulator (GOL vs. IFX p < 0.001, and p > 0.05 for the other comparisons). Conclusions: In this Norwegian real-world registry study of UC patients, drug survival for biologics differed significantly in both first- and second-line treatment.